The effect of commitment, leadership and compensation on job satisfaction and performance of government apparatus in West Sulawesi Province - Atika Atika; Basri Modding; Baharuddin Sammaila; Hamzah Hafied (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2019)
The apparatus performance is a fundamental problem affecting the organizational performance of West Sulawesi Province Government. Many factors affect it, both individual characteristics and organizational, especially commitment, leadership, compensation and job satisfaction. This study analyzes the effect of organizational commitment, leadership and compensation on job satisfaction and the impact on apparatus performance. The study was conducted on 358 respondents of Government apparatus in West Sulawesi Province. The data was collected by five point Likert scale and analyzed by Structural Equation Model (SEM). The study results found that commitment and leadership affect on job satisfaction and apparatus performance. While compensation only affects job satisfaction and does not affect on performance apparatus.